ANALISIS PROMOSI PENJUALAN DAN PENINGKATAN VOLUME PENJUALAN SEPEDA MOTOR MERK YAMAHA PADA CV. SINAR UTAMA DI SAMARINDA - -, Farida - (EKONOMIA, 2014)
The problem of this study is whether promotions significant effect on the volume of sales, of the variables examined examined whether promotion variables have the most dominant and significant effect on the volume of sales in sales in Cv. Main beam Mangkupalas Samarinda Seberang.Ie marketing management analysis, planning, implementation and monitoring of program that aim to inflict the intented market exchange with a view to achieving the company’s goals. The hypothesis of this study is a significant effect on the Sales Promotion on Sales Volume Cv. Main beam Mangkupalas Samarinda Seberang.The data has been collected in the analysis using simple linear regression. The formula used to calculate the simple linear regression is: Y = a + bx. Authors using SPPS.Based on the analysis and discussion, show that the Promotion significant effect on the volume of sales. These findings support the hypothesis that affect the sales volume